Patient Satisfaction Level of Enhanced Recovery after C-Section at Abby Maternal and Child Hospital Lhokseumawe - Anna Millizia; Adi Rizka; Wizar Putri Mellaratna (HM Publisher, 2023)
Enhanced recovery after surgery (ERAS) is a multimodal approach to optimize perioperative management and postoperative outcome. In the field of obstetrics, the implementation of ERAS, called enhanced recovery after caesarian section (ERACS), is still quite lagging behind compared to other surgical specialties. This study aims to describe patient satisfaction with the ERACS method in anesthesia services at Abby Maternal and Child Hospital, Lhokseumawe. This study is a descriptive study and was conducted on post-cesarean section patients who were treated at Abby Maternal and Child Hospital, Lhokseumawe. The sampling technique used purposive sampling technique with a population of 46 respondents. The results of the analysis showed that 45 respondents (97.8%) were satisfied with the service at the hospital after undergoing a cesarean section with the ERACS method of pain management at Abby Maternal and Child Hospital, Lhokseumawe. Most respondents experienced mild pain (87%) and were able to mobilize early after cesarean section and carry the baby for breastfeeding (95.7%). The side effects felt were nausea and vomiting in 8 patients (17.4%) and chills in 11 patients (23.6%). In conclusion, the majority of respondents stated that they were satisfied with the ERACS method of pain management at postoperative C-sections.